Collagenous colitis: the clinical and morphological features. Issue 680 (June 1982) - Colina, F.; Munoz-Yagüe, M. T.; Solis-Herruzo, J. A.; Vazquez, G.; Perez-Barrios, A.
Abstract : A woman aged 23 years is described who had watery diarrhoea and colicky abdominal pain with normal results on sigmoidoscopy and barium enema. Rectal biopsy showed a thick layer of collagen in the lamina propria below the free epithelial surface. This lesion extended throughout the length of the descending colon. The only change revealed by electron microscopy was an increase in the thickness of the sub-epithelial collagen layer which is normally present in the colon. The maturation of the fibroblasts was normal. The lesion in this patient may be considered as a small change from the normal situation. This lesion is typical of 'collagenous colitis' of which only three other cases have as yet been published.